Urgensi Pembelajaran Menerjemah Arab-Indonesia Pada Perguruan Tinggi Agama Islam Di Indonesia - Umi Hanifah (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2018)
The progress of a nation can be achieved through translation activities. The rapid development of science began with the implementation of translation institutions which later became educational institutions. In Indonesia, translation activities from Arabic to Indonesian are focused on religious texts, ranging from the Holy Qur'an, Hadith, and Interpretation to books on da'wah, morals, and Islamic thought books. There are several problems that are often faced by Indonesian translators, including regarding difficult translation activities, substantial differences between Arabic and Indonesian, the lack of mastery of the translator towards the recipient's language, resulting in symptoms of interference, and lack of mastery of the translator's theory of translation. For this reason, translating courses need to be taught at Islamic universities in Indonesia. Learning to translate in Indonesia aims to equip students with knowledge about the theory of translation and to provide students with experience in translating various types of texts, such as religious, scientific, literary, economic, and cultural texts with various levels of difficulty. To be able to achieve this goal, the translator lecturer must have theoretical qualifications, experience, and master the source language and language of the recipient as well as well as master the culture of both languages ??namely Arabic-Indonesian